2020
DOI: 10.3390/ijms21217820
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil: The Underdog That Packs a Punch in the Fight against Cancer

Abstract: The advent of immunotherapy has had a major impact on the outcome and overall survival in many types of cancer. Current immunotherapeutic strategies typically aim to (re)activate anticancer T cell immunity, although the targeting of macrophage-mediated anticancer innate immunity has also emerged in recent years. Neutrophils, although comprising ≈ 60% of all white blood cells in the circulation, are still largely overlooked in this respect. Nevertheless, neutrophils have evident anticancer activity and can indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 256 publications
(397 reference statements)
0
19
0
Order By: Relevance
“…Inflammation is one of the hallmarks of cancer. Additionally, neutrophils are among the most important immune cells implicated in promoting tumor progression[ 40 , 41 ]. NETs participate in cancer progression by promoting the proliferation, invasion, metastasis and angiogenesis of cancer cells as well as thrombosis in numerous tumor types[ 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is one of the hallmarks of cancer. Additionally, neutrophils are among the most important immune cells implicated in promoting tumor progression[ 40 , 41 ]. NETs participate in cancer progression by promoting the proliferation, invasion, metastasis and angiogenesis of cancer cells as well as thrombosis in numerous tumor types[ 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltrating dendritic cells tend to drive tumour progression through elevating the immunosuppression and tolerance (18). Infiltrating neutrophils play pro-tumoral functions by N2-subtype polarization (19). Here, high SPP1 indicated less CD8+ T cell and B cell tumor infiltration, whereas more infiltrated neutrophils, macrophages, and myeloid dendritic cells were correlated with high SPP1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…Besides, Treffers et al [ 108 ] even disclosed that IgA antibodies were superior to IgG antibodies in killing cancer cells by PMN in combination with CD47-SIRPα checkpoint inhibitor. A comprehensive review of neutrophils in fighting against cancers has been reported by Usyannovska Avtenyuk et al [ 109 ].…”
Section: Trogocytosis Among Immune-related Cells and Tumor Cells Imentioning
confidence: 99%